Liberia - A Diagnostic of Social Protection - World Bank (Washington, DC, 2013)
In recent years, the Government of Liberia launched efforts to develop a coordinated strategy for social protection. Indeed, social protection will be one of the key policy issues addressed within the Human Development pillar of the Poverty Reduction Strategy (PRS) II. This strategy development, the objective of this paper is to inform the development of an integrated, national social protection strategy targeting the needs of 'the most neglected categories of households in Liberia'. This report is organized as follows. After the introductory first chapter, chapter two presents the profile of poverty and vulnerability in Liberia. It focuses on income poverty and economic vulnerability. Chapter three defines social protection and presents the theoretical role of social protection as a strategic policy option to address vulnerability and poverty, with a focus on the national institutional framework. Chapter four illustrates current spending in social protection programs. Chapter five reviews existing contributory programs. Chapter six outlines existing non-contributory programs with a view on the various actors (government, technical and financial partners, and key actors of civil society), the main programs, and the financial resources allocated. An analysis of their relevance, effectiveness and efficiency in order to identify best practices is also reported. Chapter seven details the coverage of social safety net (SSN) in Liberia at present. Chapter eight presents possible options for increasing or better allocating the spending on SSN in Liberia. Chapter nine suggests a multi-sectoral approach to SSN, including an analysis of the complementarily of food and cash transfers. Chapter ten provides an overview of field research conducted on the coping mechanisms and informal social protection networks used by Liberian households. Finally, the last chapter provides key policy recommendations for improving the effectiveness of existing social safety nets and the reach of the sector to protect the poor and vulnerable and respond to future crises.